Bacteriological Study and Properties of Drinking Water and Storage Tanks in Some Neighborhoods of Al-Kut City - al-Shami, Najat Juma Mohammed (American Journal of Biology and Natural Sciences, 2025)
This study has been applied on different sites in Kut city to evaluate the content of water of coliform fecal bacteria and to evaluate the ecology characteristics so (9) districts have been chosen from the right side of Tigris river in Kut and (7) districts from the left side of the same river. These samples have been taken regularly during six months from January 2018 to June 2019. The total number of E. coli bacteria has exceeded the allowed limit of the drinking water especially in Summer season which recorded a higher average for the number of bacteria (79.5 cell/100ml) for right side of the river and with the average of (67.1cell/100ml) for the left side. The failure of the sample was obvious by recording (10.79%) for those ,which were taken from right side while they ranged as (5.99%) for those in the left side of the river ,so it seems that the sample which are selected for six months from AL-Jihad district is the most failure of the right side the river. whereas, the values of physical and chemical properties can be recorded according to the water PH which showed a fluctuation in its acid state and it has less values in AL-Karemeya district which is ranged as (5.7) and its high values was in the right side in AL- Khajiya district which ranged as (8.2) and most values were within swift baseband state. The Total of dissolved material (TDS)have clear proximities in both sides and with exceeding in the values during March month which ranged as (1000mg/L) and it recorded (1018 mg/L) in the right side and (1017 mg/L) for the left side .The result of some examined sample showed that the average of chlorine is less than the allowed average while it’s higher in other areas which ranged 600mg/L.